Investigation and management of Clostridium difficile colonisation in a paediatric oncology unit. Issue 3 (March 1995) - Schuller, I; Saha, V; Lin, L; Kingston, J; Eden, T; Tabaqchali, S
Abstract : Little is known about Clostridium difficile infection in children with cancer but a presumed outbreak has previously been described. The carriage rate before admission to hospital and morbidity is reported to be high, especially in younger children. The prevalence of C difficile infection on a paediatric oncology ward was monitored from June 1991 to May 1992. Twenty eight (13%) of 214 children were found to be infected. Though the temporal distribution suggested an outbreak, polyacrylamide gel electrophoresis identified several different types. Unlike previous reports, infection appeared to be possibly endogenous or possibly environmental in origin rather than due to cross infection; the morbidity was low and age was not a determinant for infection. The duration of hospital stay and the primary diagnosis were found to be determinants for infections, those with lymphoid malignancies being at the highest risk. The diagnostic category at greatest risk were those most intensively treated, with protracted neutropenia and prolonged antibiotic exposure. Early identification of cases and prompt institution of simple control measures will prevent cross infection. It is therefore important that diarrhoea is not accepted as a normal symptom of cancer chemotherapy and stool specimens are sent for full bacteriological and viral investigation.